Evaluation of the Risk Factors for Cellulitis among Patients with Peripheral Artery Disease - Bo-Yuan Wang; Shun-Fa Yang; Ke-Hsin Ting; Yu-Hsun Wang; Ming-Chih Chou; Chao-Bin Yeh (Medicina, 2023)
Background and objectives: The objective of this study is to elucidate peripheral occlusion artery disease (PAOD) as a risk factor for cellulitis. Materials and Methods: This is a retrospective population-based cohort study. The database is the Longitudinal Health Insurance Database, which covers two million beneficiaries from the entire population of the 2010 registry for beneficiaries in Taiwan. The PAOD group is composed of patients who were newly diagnosed with PAOD from 2001 to 2014. The non-PAOD group is composed of patients who were never diagnosed with PAOD from 2001 to 2015. All patients were followed until the onset of cellulitis, death, or until the end of 2015. Results: Finally, 29,830 patients who were newly diagnosed with PAOD were included in the PAOD group, and 29,830 patients who were never diagnosed with PAOD were included in the non-PAOD group. The incidence densities (ID) of cellulitis were 26.05 (95% CI = 25.31–26.80) patients per 1000 person-years in the PAOD group and 49.10 (95% CI = 48.04–50.19) in the non-PAOD group. The PAOD group had an increased risk of cellulitis (adjusted HR = 1.94, 95% CI = 1.87–2.01) compared to the non-PAOD group. Conclusions: Patients with PAOD were associated with a higher risk of subsequent cellulitis compared to patients without PAOD.